Systematic literature and modeling review of Personal Branding - Szántó, Péter (Marketing & Menedzsment, 2023)
THE AIMS OF THE PAPER The purpose of this paper is to conceptualize a standardized model and metric for Personal Branding that can be integrated into the antecedents of the limited research in the area. It also examines if a future standardized performance measurement can be added to success factors of business development. METHODOLOGY A systematic review of the literature was undertaken during the period of September 2021 and January 2022. According to Scopus, out of the 218 relevant articles to Personal Branding published in a span of 22 years. In the approach, they were searched using related keywords and specific selection criteria. MOST IMPORTANT RESULTS While Personal Branding is a growing identified academic phenomenon, there is no widely accepted definition of Personal Branding. This needs to be conducted in order to apply frameworks for standardization. As for developing theoretical frameworks that can be used to measure the effect of PB in BD as an input and output variable. RECOMMENDATIONS By reviewing the most relevant literature, this study motivates researchers to establish a commonly accepted definition for Personal Branding. Furthermore, the introduced routes encourage researchers to 1) analyze and categorize the concept and 2) review models that can be combined with attributes of Personal Branding’s processes, providing generic inputs and outputs factors that can serve as measurable attributes in the context of the relationship between Personal Branding and Business Development.